Influence of the medications containing phospholipids on the serum immunoglobulin g level in calves during formation of colostral immunity - Golopura, S. I.; Tsvilikhovsky, M. I.; Popadiuk, B. V. (НУБіП України, 2020)
The results of the application of the medication “Membranostabil” and native phospholipid bilayer liposomes based on soybean lecithin developed by this research group for correction of serum immunoglobulin G (IgG) content in newborn calves during colostral immunity formation are presented. The indices of IgG content in blood serum of newborn calves have been investigated in dynamics - from the birth till the age of 11 days. Studies were performed on newborn calves of three groups (control, and two experimental ones) of the Ukrainian black-and-white dairy breed. The level of IgG was investigated by electrophoresis in polyacrylamide gel Quantitative estimation of protein fractions was performed by scanning the lectrophoregram, with their subsequent graphical reconstruction and calculation by relative units or area using a computer program. It is established that “Membranostabil” medication and native liposomes from phospholipid bilayer based on soybean lecithin activate transport of immunoglobulins in small intestine and promote a significant increase of content of serum IgG compared to calves of the control group. The ontent of IgG in the serum of newborns calves of both experimental groups at 6 hours of age significantly increased and remained higher throughout the duration of the experiment, except for the calves of the first experimental group at the age of 7 days, compared with calves in the control group. The dynamics with comparative analysis of serum IgG content between calves of individual groups is shown. The increase of content of serum IgG in newborn calves is one of factors preventing early immunodeficiency, sepsis, development of digestive disorders, and other diseases of young animals.
Keywords: colostral immunity; colostrum; newborn calves; membranostabil; immunoglobulin G (IgG)